Extraction of Cadmium(II) Using Cloud-Point Method and Determination by FAAS - Moghimi, Ali; Tajodini, Nilofar (Asian Journal of Chemistry, 2010)
A new, simple and versatile cloud-point extraction (CPE) methodology has been developed for type equation here for the separation and pre-concentration of cadmium. The metals in the initial aqueous solution were complexed with 2-(2-benzothiazolylazo)-2-p-cresol (BTAC ) and Triton-X-114 was added as surfactant. Dilution of the surfactant-rich phase with acidified methanol was performed after phase separation and the cadmium contents were measured by flame atomic absorption spectrometry. The variables affecting the cloud-point extraction were optimized using a Box-Behnken design. Under the optimum experimental conditions, enrichment factors of 29 and 25 were achieved for cadmium. The accuracy of the method was evaluated and confirmed by the inductively coupled plasma atomic emission spectrometric analysis. The limits of detection expressed to solid sample analysis were 0.1 μg g-1 (Cd). The precision for 10 replicate measurements of 75 μg L-1 Cd was 0.9. The method has been successfully applied to the analysis of water samples.